2016
DOI: 10.1128/iai.00506-16
|View full text |Cite
|
Sign up to set email alerts
|

A Zebrafish Model of Cryptococcal Infection Reveals Roles for Macrophages, Endothelial Cells, and Neutrophils in the Establishment and Control of Sustained Fungemia

Abstract: Cryptococcal meningoencephalitis is a fungal infection that predominantly affects immunocompromised patients and is uniformly fatal if left untreated. Timely diagnosis is difficult, and screening or prophylactic measures have generally not been successful. Thus, we need a better understanding of early, asymptomatic pathogenesis. Inhaled cryptococci must survive the host immune response, escape the lung, and persist within the bloodstream in order to reach and invade the brain. Here we took advantage of the zeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 70 publications
1
60
0
Order By: Relevance
“…In response to pathogens, macrophages can target and kill these microbes; for example, in response to the bacterial pathogen Salmonella, macrophages use LC3-associated phagocytosis to control this pathogen (Masud et al, 2019). But, in other infections, such as the bacterial pathogen B. cenocepacia (Mesureur et al, 2017) or the fungal pathogens A. fumigatus (Rosowski et al, 2018a), T. marneffei or the C. neoformans spore form (Davis et al, 2016), macrophages actually provide a protective niche for pathogen survival and growth. In sterile wounding conditions, macrophages can modulate the inflammatory microenvironment (Tsarouchas et al, 2018;Hasegawa et al, 2017;Nguyen-Chi et al, 2017), use Vegfa activation and mechanical forces to promote angiogenesis and vascular repair (Liu et al, 2016;Gurevich et al, 2018), and promote the repair and regrowth of damaged nerve tissue (Carrillo et al, 2016;Tsarouchas et al, 2018).…”
Section: Neutrophilsmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to pathogens, macrophages can target and kill these microbes; for example, in response to the bacterial pathogen Salmonella, macrophages use LC3-associated phagocytosis to control this pathogen (Masud et al, 2019). But, in other infections, such as the bacterial pathogen B. cenocepacia (Mesureur et al, 2017) or the fungal pathogens A. fumigatus (Rosowski et al, 2018a), T. marneffei or the C. neoformans spore form (Davis et al, 2016), macrophages actually provide a protective niche for pathogen survival and growth. In sterile wounding conditions, macrophages can modulate the inflammatory microenvironment (Tsarouchas et al, 2018;Hasegawa et al, 2017;Nguyen-Chi et al, 2017), use Vegfa activation and mechanical forces to promote angiogenesis and vascular repair (Liu et al, 2016;Gurevich et al, 2018), and promote the repair and regrowth of damaged nerve tissue (Carrillo et al, 2016;Tsarouchas et al, 2018).…”
Section: Neutrophilsmentioning
confidence: 99%
“…A different study of infection with the fungal pathogen C. neoformans found that when zebrafish larvae are infected with a less virulent strain and with spores instead of the yeast form of the pathogen, macrophages can play a pathogen-protective role (Davis et al, 2016). These fungal spores are phagocytosed by macrophages but later escape back into the vasculature.…”
Section: Macrophages As a Protective Niche For Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-lytic exocytosis was implicated in persistence of fungemia(10) and may be involved in brain dissemination(23). Recently, non-lytic exocytosis was implicated as part of a process whereby phagocytic cells transfer C. neoformans to endothelial cells resulting in a new mechanism for cryptococcal crossing of the blood-brain barrier(16).…”
Section: Discussionmentioning
confidence: 99%
“…Cell-to-cell transfer is generally believed to be a process different from non-lytic exocytosis, with these two events being referred to as Type III and Type II exocytosis, respectively(9), denoting the fact that all these events share in common the exit of a fungal cell from an infected macrophage. Non-lytic exocytosis has been described in mammalian(7, 8), fish(10), insect(11), and amoeba(12) cells and appears to be a highly conserved strategy for C. neoformans cells to escape host and environmental predatory phagocytic cells. Non-lytic exocytosis has been described in other pathogenic microbes, including Burkholderia cenocepacia (13), Candida albicans (14), and Mycobacterium tuberculosis (15), suggesting that it may be a widespread strategy for microbial escape from phagocytic cells.…”
Section: Introductionmentioning
confidence: 99%